Tumor-infiltrating lymphocytes predict response to neoadjuvant chemotherapy in patients with breast carcinoma - Hornychova, Helena; Melichar, Bohuslav; Tomsova, Marketa; Mergancova, Jindøiska; Urminska, Hana; Ryska, Ales (Cancer investigation, 2008)
Tumor-infiltrating leukocytes and other immunohistochemical parameters were evaluated in pretherapeutic biopsies and resection specimens in 73 patients undergoing neoadjuvant chemotherapy with doxorubicin and paclitaxel. Ten patients with pathological complete response had significantly higher p53 expression, CD3(+) lymphocyte and CD83(+) cell counts, and lower progesterone receptor expression. In the remaining 63 patients, a significant decrease in the percentage of Ki-67, vascular endothelial growth factor expression, CD68(+) monocytes, and increased CD31(+), CD34(+), and SMA(+) stromal vessels, maximal CD3(+) and CD56(+) lymphocyte, maximal and mean CD83(+) cell, maximal CD1a(+), and maximal and mean S100(+) cell counts were observed after neoadjuvant chemotherapy.
Keywords: Biomarkers, Tumor; Neoplasm Staging; Antigens, CD; lidé; Middle Aged; Adult; nádorové biomarkery; Female; Lymphocytes, Tumor-Infiltrating; imunohistochemie; nádory prsu; Breast Neoplasms; staging nádorů; neoadjuvantní terapie; Humans; Predictive Value of Tests; Immunohistochemistry; antigen Ki-67; lidé středního věku; mladý dospělý; tumor infiltrující lymfocyty; Lymphocyte Count; ženské pohlaví; Young Adult; počet lymfocytů; Aged; Neoadjuvant Therapy; dospělí; prediktivní hodnota testů; CD antigeny; Ki-67 Antigen; senioři